2010
DOI: 10.1186/1743-8462-7-1
|View full text |Cite
|
Sign up to set email alerts
|

Representations and coverage of non-English-speaking immigrants and multicultural issues in three major Australian health care publications

Abstract: BackgroundNo recent Australian studies or literature, provide evidence of the extent of coverage of multicultural health issues in Australian healthcare research. A series of systematic literature reviews in three major Australian healthcare journals were undertaken to discover the level, content, coverage and overall quality of research on multicultural health. Australian healthcare journals selected for the study were The Medical Journal of Australia (MJA), The Australian Health Review (AHR), and The Austral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 139 publications
(135 reference statements)
1
29
0
Order By: Relevance
“…The participants were divided into two groups: patients from main English‐speaking countries (Australia, Canada, New Zealand, Republic of Ireland, South Africa, the UK and the USA) and patients from other countries where English is not the principal language . Arguing that being from an NESB did not indicate disadvantage, the federal government formally replaced the term NESB with ‘culturally and linguistically diverse’ in 1996 . However, we chose to employ the old term ‘NESB’ to indicate that patients from this group might be disadvantaged in terms of access to appropriate healthcare facilities because of language and cultural barriers.…”
Section: Methodssupporting
confidence: 91%
“…The participants were divided into two groups: patients from main English‐speaking countries (Australia, Canada, New Zealand, Republic of Ireland, South Africa, the UK and the USA) and patients from other countries where English is not the principal language . Arguing that being from an NESB did not indicate disadvantage, the federal government formally replaced the term NESB with ‘culturally and linguistically diverse’ in 1996 . However, we chose to employ the old term ‘NESB’ to indicate that patients from this group might be disadvantaged in terms of access to appropriate healthcare facilities because of language and cultural barriers.…”
Section: Methodssupporting
confidence: 91%
“…15 A recent systematic review of articles published in three major Australian healthcare journals found that only 2.2% of articles were based on multicultural health issues. 16 Given the fact that 5.5 million Australians are born overseas, this figure suggests a significant under-representation of migrants in research. 16 Migrants are also under-represented in clinical trials, which often require participants to speak English fluently.…”
Section: Introductionmentioning
confidence: 99%
“…16 Given the fact that 5.5 million Australians are born overseas, this figure suggests a significant under-representation of migrants in research. 16 Migrants are also under-represented in clinical trials, which often require participants to speak English fluently. 4 Furthermore, as pointed out above, the statistics produced by the HILDA and LSAC surveys may not be truly representative of the entire Australian population because they do not include migrant communities who often have a higher prevalence of diseases by virtue of their ethnicity.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, relying on imperfect surrogates for measures not directly available in the NHS07-08 limits the strength of the conclusions regarding these particular characteristics. The proxy used for English language proficiency was migration from a country where English is not the primary spoken language, a commonly used surrogate for cultural and linguistic diversity and non-English first language 30 . We used this proxy because people migrating from non-English-speaking countries are potentially at risk of CV, irrespective of local language proficiency, because of unfamiliarity with navigating and accessing the healthcare system 31 .…”
Section: Rheumatologymentioning
confidence: 99%